Exploring story grammar structure in the book reading interactions of African American mothers and their preschool children: a pilot investigation - Harris, Yvette R.; Rothstein, Susan E. (Frontiers in Psychology, 2014)
The aim of this investigation was to identify the book reading behaviors and book reading styles of middle class African American mothers engaged in a shared book reading activity with their preschool children. To this end, the mothers and their children were videotaped reading one of three books, Julius, Grandfather and I or Somewhere in Africa. Both maternal and child behaviors were coded for the frequency of occurrence of story grammar elements contained in their stories and maternal behaviors were also coded for their use of narrative eliciting strategies. In addition, mothers were queried about the quality and quantity of book reading/story telling interactions in the home environment. The results suggest that there is a great deal of individual variation in how mothers use the story grammar elements and narrative eliciting strategies to engage their children in a shared book reading activity. Findings are discussed in terms of suggestions for additional research and practical applications are offered on ways to optimally engage African American preschool children and African American families from diverse socioeconomic backgrounds in shared book reading interactions.